2004
DOI: 10.1111/j.1525-1497.2004.1930415.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hospitalists and nonhospitalists in inpatient length of stay adjusting for patient and physician characteristics

Abstract: OBJECTIVE:To determine the independent effect of hospitalist status upon inpatient length of stay after controlling for case mix, as well as patient-level and provider-level variables such as age, years since physician medical school graduation, and volume status of provider. DESIGN:Observational retrospective cohort study employing a hierarchical random intercept logistic regression model. SETTING:Tertiary-care teaching hospital. PATIENTS:All admissions during 2001 to the department of medicine not sent initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…1 Studies demonstrate that, compared to a system where primary care physicians provide inpatient care, the hospitalist model improves efficiency while maintaining at least equal patient outcomes. [2][3][4][5][6][7][8][9][10][11] However, scant data exist as to the effects of hospitalists on patient satisfaction. 12 Understanding how care models affect patient experience is vital in the current environment of healthcare reform and performance reporting, especially in light of the Centers for Medicare and Medicaid Services' (CMS) efforts to link the patient experience to reimbursement through ''value-based'' purchasing.…”
mentioning
confidence: 99%
“…1 Studies demonstrate that, compared to a system where primary care physicians provide inpatient care, the hospitalist model improves efficiency while maintaining at least equal patient outcomes. [2][3][4][5][6][7][8][9][10][11] However, scant data exist as to the effects of hospitalists on patient satisfaction. 12 Understanding how care models affect patient experience is vital in the current environment of healthcare reform and performance reporting, especially in light of the Centers for Medicare and Medicaid Services' (CMS) efforts to link the patient experience to reimbursement through ''value-based'' purchasing.…”
mentioning
confidence: 99%
“…Of the seven publications from academic hospitalist groups that included substantial case mix information, three described only a single neurologic diagnosis, and none listed an orthopedic condition in their 15 most common diagnoses. 8,12,13,[30][31][32][33] Only one of the programs that recorded a neurologic diagnosis was based at a university hospital. 32 In comparison, our study showed that orthopedic (hip fracture) and neurologic diagnoses (syncope, acute stroke, seizure and transient ischemic attack) comprised a third of the top 15 diagnoses that hospitalists manage.…”
Section: The Case For Hospitalist-focused Trainingmentioning
confidence: 99%
“…13,14 This early experience is similar to that of medicine hospitalists who have been shown to increase value by lowering the cost of care while maintaining its quality. [15][16][17][18] In addition, medicine hospitalists have exceeded expectations in translating this experience into improved education of trainees. [19][20][21][22] Availability of neurohospitalists to residents without the added pressures of outpatient clinics or research laboratories is expected to enhance direct resident supervision and improve patient care.…”
Section: Anticipated Advantages and Disadvantages Of Neurohospitalistmentioning
confidence: 99%